A Mini Review on the Functional Biomaterials Based on Poly(lactic acid) Stereocomplex. (2nd April 2016) - Jing, Yihan; Quan, Changyun; Liu, Bo; Jiang, Qing; Zhang, Chao
ABSTRACT: Poly(lactic acid) stereocomplex (sc-PLA) prevails over homo-poly(lactic acid)s in many aspects and showed great potential as biomaterials depending on its extraordinary biological, thermal, and mechanical properties. In the past few years, sc-PLA has gained tremendous attention as a new approach to the development of new types of functional biomaterials. This paper summarizes recent progress in the application of the concept of sc-PLA in the design and fabrication of stabilized nanoparticles and in situ gelling hydrogels for biomedical applications.